Characterization of physical properties of purified glycerol under microwave irradiation - Chong,Kah Huan (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Conversion of crude glycerol to polyglycerol has been highly concerned to reduce crude glycerol as by-product. In this study, physical properties change such as density, viscosity and refractive index of glycerol towards polyglycerol synthesis was investigated under microwave irradiation. Microwave irradiation was chosen as heating source because effectively conversion of glycerol in shorter time. Initially, purification process was conducted to remove unwanted impurities in order to obtain purified glycerol. Purified glycerol has high transparency as pure glycerol compared to crude glycerol. Next, density, viscosity and refractive index of pure glycerol, purified glycerol and crude glycerol increased with increased in time range from 0-80 minutes. Increase in density, viscosity and refractive index indicated formation of polyglycerol since polyglycerol is a more viscous and heavier compound. Lastly, density, viscosity and refractive index of purified glycerol increased when increasing in catalyst concentration and microwave power. Density, viscosity and refractive index of purified glycerol increased from 1.322 g/cm3 to 1.336 g/cm3, 628 cP to 677 cP and 1.4628 to 1.4682 respectively when increasing catalyst concentration. Density, viscosity and refractive index of purified glycerol increased from 1.318 g/cm3 to 1.336 g/cm3, 631 cP to 710.5 cP and 1.4621 to 1.4689 respectively when increasing microwave power.